VILLAGE PERUBAHAN MASA JABATAN KEPALA DESA 6 TAHUN MENJADI 9 TAHUN: DAMPAKNYA TERHADAP KEUANGAN NEGARA DAN PENGELOLAAN DANA DESA - Achmadudin Rajab (Pusat Kajian Anggaran, 2023)
The ability of the village head to manage finances is still low, due to a lack of knowledge related to financial management administration. This is possible due to the short term of the office. Therefore, this paper aims to analyze the impact of changing the term of office of the village head from 6 years to 9 years on state finances and village fund management. This research uses quantitative methods with descriptive statistics. The results show that first, the 6-year term of office according to the village heads is not ideal, due to political issues in the village after the village head election. Second, the impact of changes in the term of office can save a budget of Rp17.71 trillion. Third, the main problem in the village is education, not the tenure of the village head. Therefore, policymakers should rethink the addition of the tenure of the village head. The term of office of the village head should be equalized with the terms of office of the president and vice president, as well as the five-year terms of office of members of the DPR, DPD, and DPRD.